Monetary policy, fiscal policies, and labour markets : macroeconomic policymaking in the EMU - Beetsma, Roel M. W. J. (Cambridge University Press, 2004)
Three years after the birth of the European Monetary Union (EMU) economists are still divided in assessing the ability of its key institutions to provide macroeconomic stability and foster necessary reforms. Blending empirical and theoretical data, experts offer a comprehensive survey of recent research in macroeconomic policymaking within the EMU.